Anti-atherosclerotic effects and molecular targets of ginkgolide B from Ginkgo biloba - Weile Ye; Jiaojiao Wang; Peter J. Little; Jiami Zou; Zhihua Zheng; Jing Lu; Yanjun Yin; Hao Liu; Dongmei Zhang; Peiqing Liu; Suowen Xu; Wencai Ye; et al. (Acta Pharmaceutica Sinica B, 2024)
Bioactive compounds derived from herbal medicinal plants modulate various therapeutic targets and signaling pathways associated with cardiovascular diseases (CVDs), the world's primary cause of death. Ginkgo biloba, a well-known traditional Chinese medicine with notable cardiovascular actions, has been used as a cardio- and cerebrovascular therapeutic drug and nutraceutical in Asian countries for centuries. Preclinical studies have shown that ginkgolide B, a bioactive component in Ginkgo biloba, can ameliorate atherosclerosis in cultured vascular cells and disease models. Of clinical relevance, several clinical trials are ongoing or being completed to examine the efficacy and safety of ginkgolide B-related drug preparations in the prevention of cerebrovascular diseases, such as ischemia stroke. Here, we present a comprehensive review of the pharmacological activities, pharmacokinetic characteristics, and mechanisms of action of ginkgolide B in atherosclerosis prevention and therapy. We highlight new molecular targets of ginkgolide B, including nicotinamide adenine dinucleotide phosphate oxidases (NADPH oxidase), lectin-like oxidized LDL receptor-1 (LOX-1), sirtuin 1 (SIRT1), platelet-activating factor (PAF), proprotein convertase subtilisin/kexin type 9 (PCSK9) and others. Finally, we provide an overview and discussion of the therapeutic potential of ginkgolide B and highlight the future perspective of developing ginkgolide B as an effective therapeutic agent for treating atherosclerosis.